Perencanaan Struktur Gedung Perkantoran 4 Lantai Dengan Sistem Rangka Pemikul Momen Biasa (SRPMB) Di Wilayah Sukoharjo - Pariyanto, Pariyanto; , Ir. Aliem Sudjatmiko, M.T (2016)
Sukoharjo be part of a dynamic region which is called Solo Raya, the development of industry requires the company to expand the construction of industrial premises. construction of office buildings are useful to support the activities of the industry in term of handing the information system, protect assets/property, increased production to meet market needs, as well as managing industrial activities. the purpose of this final project was to plan the structure of an office building with 4 floors bearer ordinary moment resisiting frame (OMRF) in Sukoharjo region. planning office building refers to the regulation (ISO) has published the lates government, namely ISO 1726-2016 (Planning Procedures for Earthquake Resistance for Building Structure and Non-Building) and ISO 2847-2013 (Requirements for structural concrete building Planning flats include a roof structure (roof plate), beams, columns, slabs, foundations and sloof. the location of the office building is in Sukoharjo regency with the classification of land sites including SD category (medium land), earthquake resistant building with the response modification factor (R) amounted to 3, the primacy factor Ie buildings with a value of 1.0. (quality of concrete used f'c 25 Mpa, along longitudinal reinforcement fy =400 MPa and shear (begel) fyt = 300 MPa and 320 MPa for roof plate, floor. the results show that the planning for the roof slab roof with 10 cm thick and slab with 12 cm thick, dimension 400/600 mm griders and joints dimension 200/400 mm. for column with dimentions of 600/600 mm for bottom structure using a continuous concrete slab foundations depth of -16 m with dimension poer 2,5x2,5 m.